Enhancing Peatland Classification using Sentinel-1 and Sentinel-2 Fusion with Encoder-Decoder Architecture - Zelioli, Luca; Farahnakian, Fahimeh; Farahnakian, Farshad; Middleton, Maarit; Heikkonen, Jukka (United States, 2025)
Peatland classification provides valuable information for greenhouse gas inventory and biodiversity protection. In this paper, we proposed an encoder-decoder-based architecture for peatland classification that fuses two open-source satellite data, Sentinel-1 and Sentinel-2. We show the effect of fusion by comparing the multi-modal fusion architecture with unimodals which are trained only based on one input data source. We also investigate the influence of skip connections as the main component of the encoder-decoder to recover fine-grained details that are lost during the downsampling process. The experimental results are acquired on a study area in Finland which covers a variety minerotrophic aapa mire peatlands. The results demonstrate that multi-modal architecture consistently outperforms uni-modal architectures for peatland classification. In addition, the fusion architecture with one skip connection achieved a total accuracy of 57.44%. This shows 8.51% accuracy improvement compared with the model without skip connections.
2024 27th International Conference on Information Fusion (FUSION)